Permethylpentalene chemistry - Ashley, A; Cowley, A; O'Hare, D (2007)
A rational solution-phase synthesis of a permethylpentalene (Pn*) ligand precursor for use in organometallic chemistry has been devised through the novel peripheral alkylation of the bicyclo[3.3.0]octane ring system. Tetramethylation of tetramethyl 3,7-dihydroxybicyclo[3.3.0]octa-2,6-diene-2,4,6, 8-tetracarboxylate (1) forms sterically encumbered 2 which exhibits fluxionality. Decarboxylation to 3 followed by facile double dehydrogenation using Br2 affords 4. Nucleophilic addition of the final two methyl groups necessitates the use of an organocerium reagent and work-up yields the hexamethylated hydroxy-fulvene 5. Dehydration is achieved using aprotic conditions (LiCl/DMSO) to afford the tetraene 6, an exocyclic isomer of Pn*. 6 incorporates a bicyclic vinylfulvene unit, avoiding an 8π anti-aromatic structure. Both 3 and 4 have been structurally characterised. © Wiley-VCH Verlag GmbH and Co. KGaA, 2007.